Perbandingan Sistem Pemilihan Untuk Indonesia Yang Majemuk (Komparasi Dengan Sistem Chile Dan Amerika Serikat) - Cipta, Yulvia Chandra; Indrayati, Rosita; Putri, Intan Permata (Jurnal Hukum & Pembangunan, 2023)
General elections, including the election of president and vice president, legislative members and other regional election, are a manifestation of democracy and the basic principles of the nation in Pancasila and the 1945 Constitution of the Republic of Indonesia. Indonesia currently adheres to an open proportionality election system. As time goes by and many changes occur, the electoral system adopted by Indonesia has many shortcomings, and various problems are also faced, such as identity politics and kinship politics. Based on the many differences in electoral systems in the world, the author examines two other countries, namely Chile and the United States, to see the differences and advantages of each of the electoral systems adopted. This is because the two countries are pluralistic countries. This research uses a normative method with a conceptual approach and a comparative approach which is configured into a systematic answer. Researchers found that Indonesia was right to use an open proportional electoral system, noting that Indonesia could adopt and combine several things to develop a better electoral system.